The Students' Writing Ability in Narrative Text According to Students' Writing Self-Efficacy Level - Puspita, Dela Anisa; Ahmad, Yousef Bani (Peneliti.net, 2024)
This article explores students' writing ability in narrative texts in terms of their level of writing self-efficacy categories. Using a qualitative research approach with a case study design, this study was conducted in a high school located in Karawang. Two participants were selected based on predetermined categories from 30 students. The research instruments included questionnaires, written tests, interviews, and documentation. The findings of this study indicate that students' narrative writing ability can be seen from their level of self-efficacy. This study highlights the interaction between students' perceptions of their writing ability and their actual performance in narrative writing tasks. The insights gained from this study contribute to a deeper understanding of the dynamics of students' writing skills and self-efficacy beliefs, which offers valuable implications for teaching and learning practices in the context of narrative writing education.